cuidados de enfermería en paciente con herpes zoster. - Silva Camacho, Leidy Elizabeth (2018)
We present the clinical case study of a 22-year-old patient, who comes to the doctor's office, due to initially painful and pruritic erythematous lesions in the region of her anterior thorax, which begin in her sternum surrounding the lower part of her breast right until you reach your posterior thorax without passing the midline in your dorsal region. The cephalocaudal physical examination showed multiple vesicles grouped in the shape of a cluster of grapes on an erythematous background, located on the right side of the thorax and disseminated to the dorsal region, for which a herpes zoster was diagnosed as a medical diagnosis and after a survey through the functional patterns of Marjory Gordon it is defined that the patient has four pauses affected so that the following DISCONFORT nurse diagnosis is obtained evidenced by the symptoms associated with her pathology, she was indicated the opportune treatment and the lesions disappeared as well as the associated symptoms avoiding the possible complications